Artificially synthesized fluoride-free mica crystal material

Through the ratio of fluorine-free raw materials and high-temperature roasting process, high-performance fluorine-free mica crystal materials are prepared, which solves the problem of fluoride pollution in traditional mica materials and realizes the environmental protection and high performance of the materials.

CN119706857AInactive Publication Date: 2025-03-28HENAN MOJING NEW MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411774270.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-05
Publication Date
2025-03-28
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The fluoride introduced in traditional synthetic mica materials will release toxic hydrogen fluoride gas during high-temperature calcination, causing environmental pollution and health threats, and it is difficult to meet the modern industry's demand for high-performance materials.

Method used

The ratio of fluorine-free raw materials, including quartz sand, magnesium sand, alumina, potassium silicate, potassium iodate, iron oxide, potassium carbonate, manganese carbonate and nanotitanium oxide, is used to optimize the crystal growth environment through high-temperature roasting and gradient cooling processes, and high-performance fluorine-free mica crystal materials are prepared.

Benefits of technology

It realizes the high performance and environmental protection of fluorine-free mica materials, avoids the problem of fluoride pollution, has good thermal stability, chemical stability and mechanical properties, and is suitable for a variety of rigorous industrial application scenarios.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the technical field of synthetic mica, in particular to an artificially synthesized fluoride-free mica crystal material. The artificially synthesized fluoride-free mica crystal material is prepared from the following raw materials: quartz sand, magnesia, aluminum oxide, potassium silicate, potassium iodate, iron oxide, potassium carbonate, manganese carbonate and nano titanium oxide. The high-performance and environment-friendly fluorine-free mica crystal material is successfully prepared through an innovative raw material ratio and a preparation process, the defects of a traditional mica material in environmental friendliness, stability and a preparation process are overcome, and the fluorine-free mica crystal material has remarkable technical and economic advantages.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of synthetic mica, in particular to an artificially synthesized fluorine-free mica crystal material. Background Art

[0002] Mica is an important layered silicate mineral. Due to its excellent thermal stability, chemical stability, electrical insulation and mechanical properties, it is widely used in electronics, chemicals, coatings, plastics, rubber and other fields. Traditional mica materials are mainly natural mica, but natural mica resources are limited and are easily damaged by the environment during mining and processing. In addition, the composition and properties of natural mica are greatly affected by geological conditions, making it difficult to meet the needs of modern industry for high-performance materials. Therefore, artificial synthetic mica materials have gradually become the focus of research and development.

[0003] At present, the preparation of artificial synthetic mica materials usually requires the introduction of fluoride as a flux to reduce the melting temperature and promote the growth of crystals. However, fluoride releases toxic hydrogen fluoride gas during high-temperature calcination, posing a serious threat to the environment and the health of operators. In addition, fluorine-containing mica materials may release fluoride during use, further exacerbating the problem of environmental pollution. Therefore, the development of a fluorine-free artificial synthetic mica material has become an important direction of current research.

[0004] In the preparation of fluorine-free mica materials, how to ensure the structural integrity and performance stability of mica crystals by optimizing the raw material ratio and process conditions is a key technical problem. For example, the formation of mica crystals requires strict control of the raw material ratio, calcination temperature and cooling rate to avoid the generation of crystal defects. In addition, the specific surface area, particle size distribution and purity of mica materials have an important influence on their performance in industrial applications, so these parameters need to be precisely controlled during the preparation process. Summary of the invention

[0005] In view of this, the purpose of the present invention is to propose an artificially synthesized fluorine-free mica crystal material to prepare high-performance mica materials under fluorine-free conditions and improve the crystal structure stability and environmental protection.

[0006] Based on the above purpose, the present invention provides an artificially synthesized fluorine-free mica crystal material, which is prepared from the following raw materials, by weight: 20-40 parts of quartz sand, 15-25 parts of magnesia, 8-12 parts of aluminum oxide, 5-15 parts of potassium silicate, 10-20 parts of potassium iodate, 3-8 parts of iron oxide, 2-4 parts of potassium carbonate, 0.01-0.05 parts of manganese carbonate and 0.01-0.1 parts of nano titanium oxide.

[0007] Preferably, the artificially synthesized fluorine-free mica crystal material is prepared from the following raw materials, by weight: 30 parts of quartz sand, 20 parts of magnesia, 10 parts of aluminum oxide, 10 parts of potassium silicate, 15 parts of potassium iodate, 5 parts of iron oxide, 3 parts of potassium carbonate, 0.02 parts of manganese carbonate and 0.02 parts of nano titanium oxide.

[0008] Preferably, the quartz sand is 60-100 mesh, the magnesia is 60-100 mesh, the alumina is 40-80 mesh, the potassium silicate is 40-80 mesh, the potassium iodate is 40-80 mesh, the iron oxide is 40-80 mesh, the potassium carbonate is 40-80 mesh, and the manganese carbonate is 40-80 mesh.

[0009] Preferably, the average particle size of the nano titanium oxide is 20-100 nm.

[0010] Preferably, the preparation steps of the artificially synthesized fluorine-free mica crystal material are as follows: S1: After preparing quartz sand, magnesia, aluminum oxide, potassium silicate, potassium iodate, iron oxide, potassium carbonate, manganese carbonate and nano titanium oxide, put them into a mixer to mix and obtain a mixture; S2: putting the mixed material into a high-temperature calcining furnace for melting and calcining, and cooling after calcining to obtain a mica single crystal; S3: crushing the mica single crystal, passing it through a 5-20 mesh sieve to remove large particles of impurities to obtain crushed mica crystals, and then immersing the crushed mica crystals in an 8% dilute hydrochloric acid solution, immersing and stirring at room temperature for 40-60 hours, and then putting them into a vertical stirring ball mill, controlling the water content to be 40wt%-50wt%, and stopping the grinding product particle size D50 at 5-8μm, adding water for sedimentation and classification, and further removing the unground synthetic mica to obtain an artificially synthesized fluorine-free mica crystal material.

[0011] Preferably, in step S1, the rotation speed of the mixer is 1000-1500 rpm, and the mixing time is 30-60 min.

[0012] Preferably, the temperature of the melt calcination in step S2 is 1400-1500° C., and the calcination time is 20-40 min.

[0013] Preferably, the temperature is lowered in step S2 by a gradient cooling process to room temperature at a rate of 5-15°C / h.

[0014] Preferably, the concentration of the dilute hydrochloric acid solution in step S3 is 5wt%-10wt%.

[0015] Beneficial effects of the present invention: Strong environmental protection: The artificially synthesized fluorine-free mica crystal material provided by the present invention does not contain fluorine element at all, thus avoiding the pollution problem caused to the environment by the traditional fluorine-containing mica material during the preparation and application process, and meets the requirements of green environmental protection and sustainable development.

[0016] Excellent performance: The present invention optimizes the crystal growth environment during the calcination process by introducing fluxes and modifiers such as potassium iodate, manganese carbonate and nano-titanium oxide, thereby increasing the nucleation rate and crystallinity of mica single crystals and reducing the generation of impurities. The prepared fluorine-free mica crystal material has good thermal stability, chemical stability and mechanical properties, can remain stable in high temperature, high pressure and acid-base environments, and is suitable for a variety of harsh industrial application scenarios.

[0017] Strong process controllability: The present invention adopts gradient cooling and precise temperature control technology to ensure the structural integrity and uniformity of the mica crystal and avoid crystal defect problems caused by rapid cooling.

[0018] Superior economic efficiency: The present invention is based on cheap and readily available raw materials such as quartz sand, magnesia, alumina, etc., and reduces the material preparation cost through scientific formula design and process optimization, and has good economic benefits and market competitiveness.

[0019] Broad application prospects: The artificially synthesized fluorine-free mica crystal material of the present invention can be widely used in electronics, chemical industry, coatings, plastics, rubber and other fields, especially suitable for high-performance insulating materials, high-temperature resistant coatings and high-temperature lubricants, showing important industrial application value.

[0020] In summary, the present invention successfully prepares a high-performance, environmentally friendly fluorine-free mica crystal material through innovative raw material ratios and preparation processes, overcomes the shortcomings of traditional mica materials in environmental protection, stability and preparation process, and has significant technical and economic advantages. DETAILED DESCRIPTION

[0021] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific embodiments.

[0022] Embodiment 1: S1. After 20g of quartz sand, 15g of magnesia, 8g of alumina, 5g of potassium silicate, 10g of potassium iodate, 3g of iron oxide, 2g of potassium carbonate, 0.01g of manganese carbonate and 0.01g of nano-titanium oxide were prepared, put into a mixer and mixed at a mixer speed of 1000rpm for 30min to obtain a mixture; S2. The mixture was melt-calcined in a high-temperature calcining furnace at a temperature of 1400°C for 20 min. After calcination, the mixture was cooled to room temperature at a rate of 5°C / h in the furnace to obtain a mica single crystal. S3. The mica single crystal is crushed, passed through a 10-mesh sieve, and large particles of impurities are removed to obtain crushed mica crystals. The crushed mica crystals are then immersed in a 5wt% dilute hydrochloric acid solution, and the solution is immersed and stirred at room temperature for 40 hours. The mica crystals are then put into a vertical stirring ball mill, and the water content is controlled to be 40wt%. The particle size D50 of the ground product is stopped at 5μm, and water is added for sedimentation and classification to further remove the unground synthetic mica to obtain an artificially synthesized fluorine-free mica crystal material.

[0023] Example 2 S1. After 30g of quartz sand, 20g of magnesia, 10g of alumina, 10g of potassium silicate, 15g of potassium iodate, 5g of iron oxide, 3g of potassium carbonate, 0.02g of manganese carbonate and 0.02g of nano-titanium oxide are prepared, put into a mixer and mixed at a mixer speed of 1200rpm for 45min to obtain a mixture; S2. The mixture was melt-calcined in a high-temperature calcining furnace at a temperature of 1450 ° C for 30 min. After calcination, the mixture was cooled to room temperature at a rate of 5-15 ° C / h in the furnace to obtain a mica single crystal; S3. The mica single crystal is crushed, passed through a 10-mesh sieve, and large particles of impurities are removed to obtain crushed mica crystals. The crushed mica crystals are then immersed in a dilute hydrochloric acid solution with a concentration of 8wt%, and immersed and stirred at room temperature for 48 hours. The mica crystals are then put into a vertical stirring ball mill, and the water content is controlled to be 45%. The particle size D50 of the ground product is stopped at 6μm, and water is added for sedimentation and classification to further remove the unground synthetic mica to obtain an artificially synthesized fluorine-free mica crystal material.

[0024] Embodiment 3: S1. After 40g of quartz sand, 25g of magnesia, 12g of alumina, 15g of potassium silicate, 20g of potassium iodate, 8g of iron oxide, 4g of potassium carbonate, 0.05g of manganese carbonate and 0.1g of nano-titanium oxide are prepared, put into a mixer and mixed at a mixer speed of 1500rpm for 60min to obtain a mixture; S2. The mixture was melt-calcined in a high-temperature calcining furnace at a temperature of 1500°C for 40 min. After calcination, the mixture was cooled to room temperature at a rate of 15°C / h in the furnace to obtain a mica single crystal. S3. The mica single crystal is crushed, passed through a 10-mesh sieve, and large particles of impurities are removed to obtain crushed mica crystals. The crushed mica crystals are then immersed in a 10wt% dilute hydrochloric acid solution, and immersed and stirred at room temperature for 60 hours. The mica crystals are then put into a vertical stirring ball mill, and the water content is controlled to be 50wt%. The particle size D50 of the ground product is stopped at 8μm, and water is added for sedimentation and classification to further remove the unground synthetic mica to obtain an artificially synthesized fluorine-free mica crystal material.

[0025] Performance Test: Density: The Archimedean method was used to measure the density of the artificially synthesized fluorine-free mica crystal material. The results are shown in Table 1.

[0026] Mechanical properties test: A micro-Vickers hardness tester was used to measure the hardness of the synthetic fluorine-free mica crystal material, and an electronic universal testing machine was used to test the bending strength of the synthetic fluorine-free mica crystal material. The results are shown in Table 1. Table 1 Performance test results sample <![CDATA[Density / g / cm 3 > Hardness / GPa Bending strength / MPa Example 1 2.9824 4.15 75.21 Example 2 3.0952 4.62 81.32 Example 3 2.9214 4.32 78.14 Data Analysis: From the data of Examples 1-3 in Table 1, it can be seen that the artificially synthesized fluorine-free mica crystal material prepared by the present invention has extremely high density and hardness, and its bending strength can reach 81.32MPa, indicating that the artificially synthesized fluorine-free mica crystal material has continuous fine grains. Continuous fine grains can better disperse pressure, thereby improving hardness, and as the grain size decreases, the number of grain boundaries increases, and because cracks always extend along the grain boundaries where stress is concentrated, the increase in interlaced grain boundaries can better hinder crack propagation, thereby improving bending strength.

[0027] Those skilled in the art should understand that the discussion of any of the above embodiments is merely illustrative and is not intended to imply that the scope of the present invention is limited to these examples. Under the concept of the present invention, the technical features in the above embodiments or different embodiments may be combined, the steps may be implemented in any order, and there are many other variations of the different aspects of the present invention as described above, which are not provided in detail for the sake of simplicity.

Claims

1. An artificially synthesized fluorine-free mica crystal material, characterized in that: The invention is prepared from the following raw materials by weight: 20-40 parts of quartz sand, 15-25 parts of magnesia sand, 8-12 parts of aluminum oxide, 5-15 parts of potassium silicate, 10-20 parts of potassium iodate, 3-8 parts of iron oxide, 2-4 parts of potassium carbonate, 0.01-0.05 parts of manganese carbonate and 0.01-0.1 parts of nano titanium oxide.

2. The artificially synthesized fluorine-free mica crystal material according to claim 1, characterized in that: The artificially synthesized fluorine-free mica crystal material is prepared from the following raw materials by weight: 30 parts of quartz sand, 20 parts of magnesia, 10 parts of aluminum oxide, 10 parts of potassium silicate, 15 parts of potassium iodate, 5 parts of iron oxide, 3 parts of potassium carbonate, 0.02 parts of manganese carbonate and 0.02 parts of nano titanium oxide.

3. The artificially synthesized fluorine-free mica crystal material according to claim 1, characterized in that: The quartz sand is 60-100 mesh, the magnesia is 60-100 mesh, the alumina is 40-80 mesh, the potassium silicate is 40-80 mesh, the potassium iodate is 40-80 mesh, the iron oxide is 40-80 mesh, the potassium carbonate is 40-80 mesh, and the manganese carbonate is 40-80 mesh.

4. The artificially synthesized fluorine-free mica crystal material according to claim 1, characterized in that: The average particle size of the nano titanium oxide is 20-100 nm.

5. The artificially synthesized fluorine-free mica crystal material according to claim 1, characterized in that: The preparation steps of the artificially synthesized fluorine-free mica crystal material are as follows: S1: After preparing quartz sand, magnesia, aluminum oxide, potassium silicate, potassium iodate, iron oxide, potassium carbonate, manganese carbonate and nano titanium oxide, put them into a mixer to mix and obtain a mixture; S2: putting the mixed material into a high-temperature calcining furnace for melting and calcining, and cooling after calcining to obtain a mica single crystal; S3: crushing the mica single crystal, passing it through a 5-20 mesh sieve to remove large particles of impurities to obtain crushed mica crystals, and then immersing the crushed mica crystals in an 8% dilute hydrochloric acid solution, immersing and stirring at room temperature for 40-60 hours, and then putting them into a vertical stirring ball mill, controlling the water content to be 40wt%-50wt%, and stopping the grinding product particle size D50 at 5-8μm, adding water for sedimentation and classification, and further removing the unground synthetic mica to obtain an artificially synthesized fluorine-free mica crystal material.

6. The artificially synthesized fluorine-free mica crystal material according to claim 5, characterized in that: In step S1, the rotating speed of the mixer is 1000-1500 rpm, and the mixing time is 30-60 min.

7. The artificially synthesized fluorine-free mica crystal material according to claim 5, characterized in that: The temperature of the melt calcination in step S2 is 1400-1500° C., and the calcination time is 20-40 minutes.

8. The artificially synthesized fluorine-free mica crystal material according to claim 5, characterized in that: The temperature in step S2 is gradually lowered to room temperature at a rate of 5-15°C / h.

9. The artificially synthesized fluorine-free mica crystal material according to claim 5, characterized in that: The concentration of the dilute hydrochloric acid solution in step S3 is 5wt%-10wt%.